ANALISIS KELAYAKAN FINANSIAL USAHA PENGGEMUKAN SAPI SIMMENTAL PERANAKAN ONGOLE DAN FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP JUMLAH KEPEMILIKAN PADA PETERNAKAN RAKYAT DI KABUPATEN KARANGANYAR - Josua Sahala (Buletin Peternakan, 2016)
This study was done to determine the financial feasibility of beef cattle fattening and the factors affecting on amount of cattle ownership of small scale farmer in Karanganyar District. The location quotient (LQ) selected were Jenawi, Jatiyoso and Mojogedang sub-districts. Sampling respondents were determined by purposive sampling of 40 SimPO cattle farmers. Survey method was adopted to collect the primary data from respondents and the secondary data from relevant offices. The criteria for feasibility analysis was net present value (NPV), benefit cost ratio (BCR), internal rate of return (IRR), followed by payback period of credit (PPC) and break event point (BEP). Multiple regression linear analysis was used to determine the factors that influence the number of cattle ownership. The results of analysis showed that financially SimPO cattle fattening with a period of 5 years and a discount factor of 12%/year was feasible. Regression analysis showed that there were positive effects (P<0.01) of agricultural land, beef cattle business experience and the number of labour on the number of beef cattle ownership. It was concluded that SimPO cattle fattening in Karanganyar was feasible. (Key words: Break event point, Fattening, Simmental Ongole Crossbred cattle, Financial analysis, Multiple regresion linear analysis, Small scale farmer)